Nie(równość) szans edukacyjnych zdolnych podopiecznych pieczy instytucjonalnej - Ruszkowska, Marzena; Zdunkiewicz, Piotr (Rocznik Pedagogiczny, 2022)
The issue of abilities and talents is of great importance, as young people are required to possess a solid education and creativity, which talented people can certainly benefit from, especially if they are surrounded by adequate education and a supportive family environment. Unfortunately, the latter aspect is lacking in children in foster care (especially in institutional care). The researches and analyses of analyzed phenomenon allow to conclude that children in foster care are often a neglected group in terms of upbringing, education, personal models, values, and life priorities. Foster care should be an educational environment designed to compensate for deficiencies in the care, upbringing, or education of the child entrusted to it, including gifted children. Research on the educational opportunities for gifted foster care children was carried out in 6 Polish voivodeships: Lublin, Warmia-Masuria, Podlasie, Subcarpathia, Świętokrzyskie and Masovia, over a two years period – from April 2018 to June 2020. The research was quantitative and qualitative in nature. It allowed authors to conclude that a gifted child in institutional care faces numerous problems, including the lack of adequate support from both educational institutions and the foster care system in developing passions, interests, and abilities.